Abundance, diversity and community characterization of aquatic Coleoptera in a rice field of Northeastern Argentina - Gómez Lutz, María Constanza (2015)
Rice fields occupy large areas in Northeastern Argentina, and in Corrientes this widespead activity has become a feature in the landscape, as it is one of the main producing provinces. The aquatic Coleoptera is part of the fauna inhabiting these artificial environments but little is known about this group in irrigated rice fields. The aims of this study were to determine the diversity and species richness of coleopterans in a typical rice field, and to characterize the community of water beetles through different abundance models. For this, samples were collected from an active rice field located in "El Sombrero" town, in Corrientes Province, between November 2011 and April 2012. An entomological net of 30 cm diameter was used, and species richness, diversity and equitability were calculated monthly; besides, the community composition was characterized by means of rank-abundance models. A total of 74 species of aquatic coleopterans were identified. January and February resulted the months with the highest diversity. The aquatic Coleoptera species found in most of the sampled months were adjusted to the logarithmic rank-abundance model. The data suggests that, if it is properly managed, rice cropping in Northeastern Argentina can support a diverse aquatic coleopteran fauna.